Additional role of liver stiffness measurement in stratifying residual hepatocellular carcinoma risk predicted by serum biomarkers in chronic hepatitis B patients under antiviral therapy. Issue 12 (December 2018) - Song, Byeong G.; Sinn, Dong H.; Chi, Sangah; Kim, Kyunga; Kang, Wonseok; Gwak, Geum-Youn; Paik, Yong-Han; Choi, Moon S.; Lee, Joon H.; Koh, Kwang C.; Paik, Seung W.
Abstract : Background: The risk of hepatocellular carcinoma (HCC) remains among patients who are treated with antiviral therapy (AVT). The degree of liver fibrosis has been suggested as an important biomarker to stratify the risk of developing HCC. We tested whether liver stiffness (LS) measured using transient elastography is useful over two noninvasive serum biomarkers of fibrosis [the aspartate aminotransferase to platelet ratio index (APRI) and fibrosis-4 (FIB-4)]. Patients and methods: A retrospective cohort of 1014 CHB patients who were under AVT with nucleos(t)ide analogs for at least a year was analyzed. The risk of HCC development according to serum biomarkers (APRI and FIB-4) and LS was compared. Results: The HCC risk was higher for those with a higher degree of liver fibrosis, as estimated by the LS, APRI, and FIB-4. When the two serum biomarkers were used to group the patients, the 3-year HCC incidence rates were 7.3, 3.0, and 1.3% for both high APRI (≥0.5) and FIB-4 (≥1.45) scores, either a high APRI or FIB-4 score, and both low APRI and FIB-4 scores, respectively ( P< 0.001). Among the 758 patients with discordant or both low APRI and FIB-4 scores, the LS value was high (>6) for a significant proportion of the patients (39.9%). The HCC risk was significantly different according to the LS value (3-year HCC incidence rate of 1.1, 2.0, and 6.8% for LS <6, 6–9, and >9, respectively, P <0.001). Conclusion: Among CHB patients under AVT, LS could stratify risk for HCC, including patients with discordant or both low APRI and FIB-4 score. This finding indicates that LS measurement plays an additional role over the serum biomarkers in stratifying the residual risk of HCC.